Comparison of predicted and actual dermatitis generated from computed tomography images and dose distribution maps - Yasuhide Miyabe; Saori Oshiro; Hiroto Seki; Yusuke Muroi; Eriko Kawashima; Megumi Hosoda; Kento Ohashi; Hiromu Yamanaka; Mingliang Shao; Hiromi Sugawara; Jyunetsu Mizoe; Ritsuko Komaki (Technical Innovations & Patient Support in Radiation Oncology)
Anticipating the onset, location and severity of radiation dermatitis before radiotherapy can aid in dermatological care. This study developed a method for creation of a prediction diagram for dermatitis and conducted a comparative verification between the prediction diagram and actual patient condition. The prediction diagram involved converting skin doses into 2 Gy fractionated equivalent doses using α/β of 10.0, defining regions of interest (ROIs) from 20-50 Gy at 10 Gy intervals. Overlaps between these ROIs at each dose level and the skin (external) was sequentially color-coded as blue, yellow, red, and purple. The study included four patients: two underwent head and neck treatment and two received neck and chest treatment. This approach involved a visual assessment comparing the prediction diagram with skin photographs captured at the end of treatment. Nurses marked skin sites corresponding to grades 1 and 2 on photographs, assessing their correlation with the predicted range. Visual assessment results were largely positive, although one patient exhibited slightly lower scores. Results revealed a correlation between grade 1 skin reactions and the 20 Gy regions. Grade 2 reactions were observed in regions near 30 and 40 Gy. Although discrepancies between prediction diagram and actual skin symptoms were observed in patients, a broad agreement was evident. The prediction diagram cannot accurately predict radiation dermatitis, as it does not account for skin symptoms unrelated to the dose. However, the diagram is significant as it provides physicians, nurses, and patients with concise and visually comprehensible information regarding the location of dermatitis.